Osteosarcoma in the Skull of a Holstein Heifer - Micheloud, Juan F.; Guidi, María G.; Gimeno, Eduardo J. (Brazilian Journal of Veterinary Pathology, 2015)
A-2-year-old heifer showed a mass on the frontal part of the skull. Cytological analysis displayed pleomorphic, polyedric and fusiform cells with extracellular hyaline material. Histologically, the excised mass showed proliferation of spindle-to-polyhedral cells that exhibited anisocytosis and anisocaryosis. Osteoid substance was demonstrated by Masson´s thricromic stain. Tumoral cells and osteoid expressed osteocalcin. This case report communicates a very rare osteosarcoma in the corneal process of a young heifer. As the heifer was previously dehorned, it is possible that this procedure was a predisposing factor for malignant growth.